Idaho State Building, Alaska Yukon Pacific Exposition, Seattle, 1909 - Bradley, Levi (1909)
Bradley 80 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number